Direct protein-lipid interactions shape the conformational landscape of secondary transporters. Issue 1 (December 2018) - Martens, Chloe; Shekhar, Mrinal; Borysik, Antoni J.; Lau, Andy; Reading, Eamonn; Tajkhorshid, Emad; Booth, Paula; Politis, Argyris
Abstract Secondary transporters undergo structural rearrangements to catalyze substrate translocation across the cell membrane – yet how such conformational changes happen within a lipid environment remains poorly understood. Here, we combine hydrogen-deuterium exchange mass spectrometry (HDX-MS) with molecular dynamics (MD) simulations to understand how lipids regulate the conformational dynamics of secondary transporters at the molecular level. Using the homologous transporters XylE, LacY and GlpT fromEscherichia coli as model systems, we discover that conserved networks of charged residues act as molecular switches that drive the conformational transition between different states. We reveal that these molecular switches are regulated by interactions with surrounding phospholipids and show that phosphatidylethanolamine interferes with the formation of the conserved networks and favors an inward-facing state. Overall, this work provides insights into the importance of lipids in shaping the conformational landscape of an important class of transporters. Secondary transporters catalyse substrate translocation across the cell membrane but the role of lipids during the transport cycle remains unclear. Here authors used hydrogen-deuterium exchange mass spectrometry and molecular dynamics simulations to understand how lipids regulate the conformational dynamics of secondary transporters.